Pengaruh Literasi Keuangan, Sikap Keuangan, dan Kepribadian terhadap Perilaku Pengelolaan Keuangan pada Pelaku UMKM Kelurahan Gedong, Jakarta Timur - Amelia Amelia (Jurnal Maksipreneur, 2022)
This research aimed to determine the effect of financial literacy on financial management behavior, the influence of financial attitudes on financial management behavior, and the influence of personality on financial management behavior in MSME actors in Gedong Village, East Jakarta, Jakarta Special Capital Region. This research is included in associative causal research. The subjects of this study were 96 wholesale and retail SMEs in a car and motorcycle repair shop in Gedong Village, East Jakarta. Data collection techniques using a questionnaire. Validity and reliability tests were conducted on 96 MSME respondents in Gedong Village, East Jakarta. The analysis prerequisite test includes a linearity test, multicollinearity test, and heteroscedasticity test. The method of data analysis used in this research is multiple linear regression. The results showed that financial literacy, financial attitude, and personality variables have a positive and significant effect on financial management behavior.